2016
DOI: 10.1136/bmjresp-2016-000162
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastrointestinal dysmotility and complications detected by abdominal plain films after lung transplantation: a single-centre cohort study

Abstract: Introduction and AimsGastrointestinal (GI) complications such as gastric retention (GR) and constipation are common after lung transplantation (LT). Abdominal plain films (APFs) are a low-cost diagnostic tool to detect impaired GI function. The goal of our study was to assess the prevalence of GI pathology seen on APF in lung transplant recipients (LTRs) and to identify associated risk factors.MethodsRetrospective analysis of consecutive LTRs followed up between 2001 and 2013. Demographic, radiographic and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Prior studies examining the prevalence of DGE following lung transplantation are quite varied, and discrepant, with reported ranges from 23% to 91% . The discrepancy in these studies is most notably due to their small sample size and in some instances, their DGE defining cut‐offs based on their respective, institution‐specific SGE study protocols . For example, Bodet‐Milin et al examined 30 patients and found that DGE was prevalent in 67% of patients pre‐lung transplant and 97% of patients post‐lung transplant, more frequently observed in patients with end‐stage CF.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior studies examining the prevalence of DGE following lung transplantation are quite varied, and discrepant, with reported ranges from 23% to 91% . The discrepancy in these studies is most notably due to their small sample size and in some instances, their DGE defining cut‐offs based on their respective, institution‐specific SGE study protocols . For example, Bodet‐Milin et al examined 30 patients and found that DGE was prevalent in 67% of patients pre‐lung transplant and 97% of patients post‐lung transplant, more frequently observed in patients with end‐stage CF.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study of 198 lung transplant recipients found a statistically significant association of diabetes with gastric retention, detected by abdominal plain films, and whose prevalence progressively increased over time following lung transplantation. Moreover, proportionally, almost half the patients had cystic fibrosis . In these contexts, it may be difficult to accurately assess the role of lung transplantation in the pathogenesis of DGE in these two specific populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations